2015
DOI: 10.1590/s1806-92902015000900002
|View full text |Cite
|
Sign up to set email alerts
|

Performance and digestibility of steers fed by-product of fresh passion fruit or sorghum silage, with and without concentrate supplementation

Abstract: -The objective of this study was to evaluate the nutritive value of passion fruit by-product for cattle, contrasting the results with those found with sorghum silage. Four treatments were then constituted, comprising the combinations of the two roughages and the two levels of supplementation (with or without), in a completely randomized design with four animals per treatment. The considered variables included: feed intake, digestibility coefficients of the diets, and live weight gain of the animals. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The CP contents were thus higher in the silage with the addition of PBP as compared with the other byproducts, as also evidenced by other authors (Cruz et al, 2011;Alves et al, 2015;Lira Junior et al, 2018). Of all three evaluated by-products, CBP provided the lowest CP levels in the silage.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The CP contents were thus higher in the silage with the addition of PBP as compared with the other byproducts, as also evidenced by other authors (Cruz et al, 2011;Alves et al, 2015;Lira Junior et al, 2018). Of all three evaluated by-products, CBP provided the lowest CP levels in the silage.…”
Section: Resultssupporting
confidence: 77%
“…47, 57.98, 50.70, and 20.60% and 4.28 Mcal kg -1 , respectively. The passion fruit by-product originates in agribusiness and has potential for use in ruminant feeding thanks to its pectin, mineral, vitamin and considerable protein content, which enables it to improve the nutritional value of the produced silage (Cruz et al, 2011;Alves et al, 2015;Bonfá et al, 2015). It is supplied by some industries for the production of compost.…”
Section: Introductionmentioning
confidence: 99%
“…Alves et al. () concluded that feeding cattle with passion fruit peel resulted in a higher feed intake and higher weight gain. Also, the coefficients of digestibility of dry matter, organic matter, crude protein, and the digestibility coefficient of neutral detergent fiber from passion fruit byproducts were higher than those observed with the sorghum silage.…”
Section: Wastes and Byproducts From Tropical Fruits And Their Currentmentioning
confidence: 99%
“…Similarly, the mixture between grass and passion fruit peel could be an efficient and environmental acceptable way to preserve feeds in order to sustain the productivity of the herds during the dry season (Espinoza et al, 2017). Alves et al (2015) concluded that feeding cattle with passion fruit peel resulted in a higher feed intake and higher weight gain. Also, the coefficients of digestibility of dry matter, organic matter, crude protein, and the digestibility coefficient of neutral detergent fiber from passion fruit byproducts were higher than those observed with the sorghum silage.…”
Section: Passion Fruit (Passiflora Edulis)mentioning
confidence: 99%
“…In this respect, by-products of fruits such as passion fruit have been constantly evaluated mainly in terms of their adequate level of inclusion in ruminant diets. In grass silage, these byproducts have shown good results (Alves et al, 2015;Bonfá et al, 2015;Lira Júnior et al, 2018).…”
Section: Introductionmentioning
confidence: 99%